2018
DOI: 10.14393/bj-v34n6a2018-39879
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal potential of essential oils of Ageratum fastigiatum, Callistemon viminalis and Schinus terebinthifolius

Abstract: Some essential oils are rich in nematicidal compounds and can be used for the management of plant-parasitic nematodes. Laboratory and field studies aiming to evaluate the efficiency of this compounds are necessary. The objective of this research was to assess the nematicidal potential of essential oils from leaves of Ageratum fastigiatum and Callistemon viminalis, and green and mature fruits of Schinus terebinthifolius on the root-knot nematode Meloidogyne javanica. In laboratory, the essential oil of S. tereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The EO extracted from S. terebinthifolius green fruit, constituted of a high concentration of terpenes such as terpinene-4-ol, α-terpinene, γ-terpinene, and α-terpineol, led to an 82-86% reduction in M. javanica hatching and increased juvenile mortality by 300%. However, field application did not effectively control M. javanica in lettuce when infestation levels were high (555 J2/100 cm 3 of soil) [54]. Laquale et al [40] reported on the nematicidal potential of γ-terpinene, which effectively controlled M. incognita in vitro and in soil.…”
Section: Other Compoundsmentioning
confidence: 99%
“…The EO extracted from S. terebinthifolius green fruit, constituted of a high concentration of terpenes such as terpinene-4-ol, α-terpinene, γ-terpinene, and α-terpineol, led to an 82-86% reduction in M. javanica hatching and increased juvenile mortality by 300%. However, field application did not effectively control M. javanica in lettuce when infestation levels were high (555 J2/100 cm 3 of soil) [54]. Laquale et al [40] reported on the nematicidal potential of γ-terpinene, which effectively controlled M. incognita in vitro and in soil.…”
Section: Other Compoundsmentioning
confidence: 99%
“…Gonçalves et al (2011) chemically evaluated the leaves and inflorescences of A. fastigiatum collected in the city of Diamantina (state of Minas Gerais) and verified, by means of gas chromatography mass spectrometry (GC-MS), the presence of triterpenes and steroids. The essential oil of of A. fastigatum leaves in the management of plant-parasitic nematode Meloidogyne javanica, however the results showed that the plant's essential oil does not control M. javanica in lettuce (BORGES et al, 2018). Avelar-freitas et al (2013) also evaluated the toxic effect of the A. fastigiatum ethanolic extract on Rhodnius nasutus (Stål 1859), the vector of Chagas disease.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Such plant extract showed toxicity higher than 70% in S. frugiperda eggs. Borges et al (2018) evaluated the potential of the essential oil…”
Section: Pest Control and Insecticidal Effectmentioning
confidence: 99%
“…In one of the few studies, Schwengber et al (2017) reported the effect of the essential oil of this plant against Pratylenchus zeae in the greenhouse. Borges et al (2018) also related to the suppression of root-knot nematode by S. terebinthifolius essential oil. It is likely that nematicidal compounds of S. terebinthifolius are concentrated in the essential oils.…”
Section: Gomes Va Et Almentioning
confidence: 99%
“…Here, we found that C. canjerana extracts and purified substances inhibit hatching of M. incognita J2, while S. terebinthifolius extracts kill the active forms of the nematode. These results should stimulate further research to evaluate whether formulations containing these extracts and compounds can be useful for the management of root-knot nematode under field conditions (Borges et al 2018). Extracts and purified substances of Cabralea canjerana inhibit hatching and extracts of Schinus terebinthifolius kill juveniles of meloidogyne incognita…”
Section: Gomes Va Et Almentioning
confidence: 99%